Carotid Intraplaque Hemorrhage Imaging at 3.0-T MR Imaging: Comparison of the Diagnostic Performance of Three T1-weighted Sequences(1) - Ota, Hideki (Radiological Society of North America, Inc., 2010)

(untitled)
PURPOSE: To compare the diagnostic performances of three T1-weighted 3.0-T magnetic resonance (MR) sequences at carotid intraplaque hemorrhage (IPH) imaging, with histo logic analysis as the reference standard. MATERIALS AND METHODS: Institutional review board approval and informed consent were obtained for this HIPAA-compliant study. Twenty patients scheduled for carotid endarterectomy underwent 3.0-T carotid MR imaging, including two-dimensional fast spin-echo, three-dimensional time-of-flight (TOF), and three-dimensional magnetization-prepared rapid acquisition gradient-echo (RAGE) sequences. Two reviewers blinded to the histologic findings assessed the presence, area, and signal intensity of IPH with each sequence. Detection statistics (sensitivity, specificity, and Cohen κ values) and agreement between area measurements (Pearson correlation coefficient [r] values) were calculated for each sequence. RESULTS: When all 231 available MR sections were included for analysis, the magnetization-prepared RAGE (κ = 0.53) and fast spin-echo (κ = 0.42) sequences yielded moderate agreement between MR and histologic measurements, while the TOF sequence yielded fair agreement (k = 0.33). However, when 47 sections with either small IPHs or heavily calcified IPHs were excluded, sensitivity, specificity, and κ values, respectively, were 80%, 97%, and 0.80 for magnetization-prepared RAGE imaging; 70%, 92%, and 0.63 for fast spin-echo imaging; and 56%, 96%, and 0.57 for TOF imaging. MR imaging–histologic analysis correlation for IPH area was highest with magnetization-prepared RAGE imaging (r = 0.813), followed by TOF (r = 0.745) and fast spin-echo (r = 0.497) imaging. The capability of these three sequences for IPH detection appeared to be in good agreement with the quantitative contrast of IPH versus background plaque tissue. CONCLUSION: The magnetization-prepared RAGE sequence, as compared with the fast spin-echo and TOF sequences, demonstrated higher diagnostic capability for the detection and quantification of IPH. Potential limitations of 3.0-T IPH MR imaging are related to hemorrhage size and coexisting calcification. © RSNA, 2010